In Situ Regolith Seismic Velocity Measurement at the InSight Landing Site on Mars. Issue 10 (30th September 2022) - Brinkman, Nienke; Schmelzbach, Cédric; Sollberger, David; Pierick, Jan ten; Edme, Pascal; Haag, Thomas; Kedar, Sharon; Hudson, Troy; Andersson, Fredrik; van Driel, Martin; Stähler, Simon; Nicollier, Tobias; et al.
Abstract: Interior exploration using Seismic Investigations, Geodesy and Heat Transport's (InSight) seismometer package Seismic Experiment for Interior Structure (SEIS) was placed on the surface of Mars at about 1.2 m distance from the thermal properties instrument Heat flow and Physical Properties Package (HP 3 ) that includes a self‐hammering probe. Recording the hammering noise with SEIS provided a unique opportunity to estimate the seismic wave velocities of the shallow regolith at the landing site. However, the value of studying the seismic signals of the hammering was only realized after critical hardware decisions were already taken. Furthermore, the design and nominal operation of both SEIS and HP 3 are nonideal for such high‐resolution seismic measurements. Therefore, a series of adaptations had to be implemented to operate the self‐hammering probe as a controlled seismic source and SEIS as a high‐frequency seismic receiver including the design of a high‐precision timing and an innovative high‐frequency sampling workflow. By interpreting the first‐arriving seismic waves as a P‐wave and identifying first‐arriving S‐waves by polarization analysis, we determined effective P‐ and S‐wave velocities of v P = 11 9 − 21 + 45 v_P=119_-21^+45 m/s and v S = 6 3 − 7 + 11 v_S=63_-7^+11 m/s, respectively, from around 2, 000 hammer stroke recordings. These velocities likely represent bulk estimates for the uppermost several 10s of cm of regolith. An analysis of the P‐wave incidence angles provided an independent v P / v S ratio estimate of 1.8 4 − 0.35 + 0.89 1.84_-0.35^+0.89 that compares well with the traveltime based estimate of 1.8 6 − 0.25 + 0.42 1.86_-0.25^+0.42 . The low seismic velocities are consistent with those observed for low‐density unconsolidated sands and are in agreement with estimates obtained by other methods. Plain Language Summary: In the framework of the NASA Interior exploration using Seismic Investigations, Geodesy and Heat Transport (InSight) mission, two scientific instruments were placed on the surface of Mars: A seismometer to detect signals from marsquakes and other sources generating seismic (elastic) waves and a self‐hammering temperature sensor that was designed to penetrate the Martian subsurface. The hammering of the temperature sensor generated vibrations that were measured by the seismometer and could be used to determine the elastic parameters of the shallow subsurface of Mars. We found low seismic velocities for the shallowest several tens of cm that are typical for low‐density loose sands. This information is important to further study the local geological setting at the InSight landing site and the shallow Martian subsurface in general. Key Points: Seismic signals from the Heat flow and Physical Properties Package mole provide a unique opportunity to study the shallow regolith First‐arrival traveltimes and P‐wave incidence angles constrain elastic parameter estimates Low seismic velocities are consistent with unconsolidated low‐density sand